Second primary malignancies following CAR T-cell therapy in patients with hematologic malignancies - Elvira Umyarova; Charles Pei; William Pellegrino; Qiuhong Zhao; Nidhi Sharma; Don Benson; Francesca Cottini; Evandro Bezerra; Jonathan Brammer; Naresh Bumma; Hannah Choe; Nathan Denlinger; et al. (Journal of Hematology & Oncology)
Abstract Chimeric antigen receptor T-cell (CAR-T) therapy has transformed the management of patients with relapsed/refractory (R/R) hematologic malignancies, including B-cell lymphomas and multiple myeloma (MM). While data pertaining to the efficacy and toxicity associated with CAR-T have been widely reported, there are limited data on long-term complications. We retrospectively analyzed 246 patients treated with CAR-T for R/R B-cell lymphoma (n = 228) and MM (n = 18) at Ohio State University from 2016 to 2022, with a minimum of two years of follow-up. The median age was 66 years, and the median number of prior treatments was four. With a median follow-up of 38 months (range 11–66), 21 patients (8.5%) developed a second primary malignancy (SPM), with non-melanoma skin cancer being the most common (52%), followed by hematologic malignancies (33%) and non-skin solid tumors (14%). Squamous cell carcinoma accounted for 38% of skin cancers, while myelodysplastic syndrome and acute myeloid leukemia were the predominant hematologic malignancies. Solid tumors included bladder, prostate, and breast cancer. The distinct pattern of SPMs suggests potential CAR-T-related risks, warranting vigilant post-treatment surveillance. Further studies are necessary to elucidate underlying mechanism and predictive factors and guide long-term management of SPM risk in CAR-T survivors.